Analisis penentuan harga pokok produksi sebagai dasar penetapan harga jual dengan pendekatan Full Costing (Studi kasus Meubeul Murah Jepara Group, Toro, Kabupaten Belu) - Mali, Maria Hernie; Dethan, Minarni A; Denu, Yohanes (ARKA INSTITUTE, 2022)
This study aims to determine the calculation of the cost of production in determining the selling price using the full costing method. The research approach in this study is a quantitative approach. The type of this research is case study research. The object of this research is Murah Jepara Group furniture located in Toro, Belu Regency. The data collection methods in this research are observation, interviews, and documentation.The data analysis technique used is descriptive with full costing method. The calculation result show that the calculation of the cost of production and selling price with the full costing method is higger than using the company method. The difference in selling prices in 2019 was Rp244,623.91. In 2020 the difference in the selling price was Rp232,181.97. In 2021 the difference in the selling price Rp220,668.35. The full costing method imposes all production costs, both those that have a fixed and variabel effect on the produc,in addition to production costs, the full costing method also charges non production costs in determining the selling price,while the company’s method has not charged the overall factory overhead costs incurred in the production process and the company has not charged non-production costs in calculating the sellig price